Nanoscopic insights into the surface conformation of neurotoxic amyloid β oligomers. Issue 37 (8th June 2020) - Banchelli, Martina; Cascella, Roberta; D'Andrea, Cristiano; Cabaj, Leszek; Osticioli, Iacopo; Ciofini, Daniele; Li, Mai Suan; Skupień, Krzysztof; de Angelis, Marella; Siano, Salvatore; Cecchi, Cristina; Pini, Roberto; et al.
Abstract : Unraveling characteristic structural determinants at the basis of Aβ42 oligomers' neurotoxicity by a sub-molecular SERS investigation of their surface. Abstract : Raman spectroscopy assisted by localized plasmon resonances generating effective hot spots at the gaps between intertwined silver nanowires is herein adopted to unravel characteristic molecular motifs on the surface of Aβ42 misfolded oligomers that are critical in driving intermolecular interactions in neurodegeneration.